2008
DOI: 10.1016/j.virol.2007.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of B lymphocytes by cmvIL-10 but not LAcmvIL-10

Abstract: Human cytomegalovirus (HCMV) is a widespread pathogen that establishes lifelong latent infection facilitated by numerous mechanisms for modulating the host immune system. The UL111A region of the HCMV genome encodes a homolog of human cellular IL-10 (hIL-10). The viral cytokine, cmvIL-10, exhibits many of the immunosuppressive properties of hIL-10. However, hIL-10 is also known to have stimulatory effects on B lymphocytes. We found that cmvIL-10 has the ability to enhance B cell proliferation, despite having o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 20 publications
1
52
1
1
Order By: Relevance
“…The evidence presented here, along with other studies on cmvIL-10 and rhcmvIL-10, lead to the following model invoking a temporal race between dissemination of virus to sites of persistence and generation of protective adaptive immune responses. Expression of rhcmvIL-10 in the control animals suppresses innate effector cells at the primary site of infection to enable dissemination to sites of persistent shedding in the salivary glands and genitourinary tract prior to development of protective adaptive responses (15,(17)(18)(19)(59)(60)(61). In contrast, vaccine-mediated neutralization of rhcmvIL-10 facilitates innate effector functions to greatly restrict robust dissemination of progeny virions until development of protective adaptive responses blocks further dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence presented here, along with other studies on cmvIL-10 and rhcmvIL-10, lead to the following model invoking a temporal race between dissemination of virus to sites of persistence and generation of protective adaptive immune responses. Expression of rhcmvIL-10 in the control animals suppresses innate effector cells at the primary site of infection to enable dissemination to sites of persistent shedding in the salivary glands and genitourinary tract prior to development of protective adaptive responses (15,(17)(18)(19)(59)(60)(61). In contrast, vaccine-mediated neutralization of rhcmvIL-10 facilitates innate effector functions to greatly restrict robust dissemination of progeny virions until development of protective adaptive responses blocks further dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…PROPERTIES OF AN HCMV LATENCY-ASSOCIATED IL-10 HOMOLOG 3747 the expression of MHC-II on Daudi human B cell lymphoblastoma cells (55), further indicating cell-type-specific immunosuppressive functions of these viral cytokines. The inability of LAcmvIL-10 to impair LPS-induced DC maturation in a manner similar to cmvIL-10 may be a consequence of differences in the structure of these two proteins.…”
Section: Vol 82 2008mentioning
confidence: 97%
“…Apart from its immunomodulatory properties on myeloid cells, cmvIL-10 has been shown to induce the growth and differentiation of a human B-cell lymphoma Daudi cell line, increasing the number of cells by 60% compared to the number of untreated cells (93). cmvIL-10 also increased the levels of hIL-10 and, to a smaller extent, IL-10R produced by B cells and did not alter surface MHC class II levels.…”
Section: Hcmv Vil-10 Expression During Productive Hcmv Infectionmentioning
confidence: 97%
“…Since vIL-10 is immunogenic in an infected host, presumably selective advantages conferred by alteration in protein sequence exceeded the costs associated with increased immune recognition by the host. It is reasonable to predict that the divergence of vIL-10 proteins from host IL-10 was a positive selection for the alteration of vIL-10 functionality, and this is supported by studies of ebvIL-10 and the latency-associated homolog encoded by HCMV (LAcmvIL-10), which demonstrate differences from hIL-10 in the repertoire of biological functions and/or the mechanism of action (28,44,59,64,93,103). However, in vitro assays have shown that the phenotype of full-length HCMV IL-10 (cmvIL-10) mimics that of hIL-10 in terms of the functional alterations to various cell types, signaling pathways, and changes in gene expression (7,8,94), and the same is true for the limited data available for other vIL-10 proteins.…”
Section: Divergence and Conservation Of Vil-10 With Host Il-10mentioning
confidence: 99%